(untitled) (Emancipação, 2016)
Resumo: O objetivo deste artigo é identificar a produção acadêmica sobre Conselhos dos Direitos da Criança e do Adolescente. Envolveu pesquisa no banco de dados da Scientific Eletronic Library Online (Scielo), da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) e na Biblioteca Digital Brasileira de Teses e Dissertações (BDTD). A publicação “Conselhos dos Direitos: desafios teóricos e práticos das experiências de democratização no campo da criança e do adolescente (2012)”, também foi utilizada como fonte de investigação. Nas pesquisas, foram identificadas 20 teses/dissertações e 06 artigos. Com as análises, observamos um aumento na produção de teses e dissertações a partir dos anos 2000, sendo a maioria delas defendida na região sudeste do Brasil. O principal foco de análise dos trabalhos é a atuação dos Conselhos dos Direitos de acordo com suas atribuições, como por exemplo, na elaboração e financiamento de políticas públicas para crianças e adolescentes. Palavras-chave: Conselhos dos Direitos. Controle Social. Criança e Adolescente. Abstract: The aim of this article is to identify the academic scope’s production about the Right Councils of Children and Adolescents. This article involved researches in the database of Scientific Electronic Library Online (Scielo), Coordination of Improvement Personnel of Higher Education and Brazilian Digital Library of Theses and Dissertations. The publication “Rights’ Councils: theoretical and practical’s challenges of democratization’s experience in children and adolescent’s issue (2012)”, also it was used as source of research. In this researches, were identified 20 theses/dissertations and 06 articles. Thereafter, in the analysis, can be observed that the production of theses and dissertations has increased from 2000s and most of them were defended in region southeastern Brazil. The main focus of analysis of the work is the acting of the Councils of Rights in accordance with their assignments, for example in the development and financing of the public policies for children and adolescents. Keywords: Rights’ Councils. Social Control. Children and Adolescents.